2005
DOI: 10.1243/095441105x28551
|View full text |Cite
|
Sign up to set email alerts
|

Automatic wheeze detection based on auditory modelling

Abstract: Abstract-Automatic wheeze detection has several potential benefits compared to reliance on human auscultation: it is experience-independent, an automated historical record can easily be kept and it allows quantification of wheeze severity. Previous attempts to detect wheezes automatically have had partial success, but have not been reliable enough to become widely accepted as a useful tool. In this paper an improved algorithm for automatic wheeze detection based on auditory modelling is developed, called the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…Two studies 28,29 used an algorithm based on short-time Fourier transformation, and one study 25 used a modification of the algorithm proposed by Shabtai-Musih et al 31 and HomsCorbera et al 32 A total of 9 studies analyzed WHs (3 studies were conducted in children), 2 studies analyzed CRs, 5,27 and one study analyzed both WHs and CRs in children. 30 Two studies detected breathing cycles automatically; one study 5 used an analogous method reported by Qiu et al, 33 and the other study 30 used the algorithm of Huq and Moussavi. 34 Only 3 studies 26,27,29 considered the breathing phases (inspiration and expiration) in the analysis of the ARSs.…”
Section: Studies Included In Review 12mentioning
confidence: 99%
“…Two studies 28,29 used an algorithm based on short-time Fourier transformation, and one study 25 used a modification of the algorithm proposed by Shabtai-Musih et al 31 and HomsCorbera et al 32 A total of 9 studies analyzed WHs (3 studies were conducted in children), 2 studies analyzed CRs, 5,27 and one study analyzed both WHs and CRs in children. 30 Two studies detected breathing cycles automatically; one study 5 used an analogous method reported by Qiu et al, 33 and the other study 30 used the algorithm of Huq and Moussavi. 34 Only 3 studies 26,27,29 considered the breathing phases (inspiration and expiration) in the analysis of the ARSs.…”
Section: Studies Included In Review 12mentioning
confidence: 99%
“…An alternative model of spectral crests was proposed in [18] with the aim of detecting only the audible sounds of wheezing. The audibility of a tonal signal masked in the noise of normal respiration was modeled by the ratio of the energy contained in the spectral crest to the energy contained in the noise of the normal respiratory sound.…”
Section: Review Of the Stft-based Wheeze Detection Algorithmsmentioning
confidence: 99%
“…The assumption is that such algorithms may provide the highest fidelity of wheeze classification, including estimation of the durations, number and frequency of the individual harmonic components composing the sound of wheezing. The algorithms differ by their spectral features: the first algorithm models the spectral crests using low-order statistical moments (mean and variance), building upon [17,19,20], and the second using energy (inspired by [18]).…”
Section: Analysis Of Implemented Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods for their detection has been proposed leaning on these characteristics as prerequisite in their analyses. Methods using short-time Fourier transform, based on a SNR threshold depending on time and frequency parameters, show good result for the detection of such abnormal sounds [24]. Other classical image processing approaches exploiting the informations given by the spectrogram allow to detect the time/frequency structure caused by the presence of continuous abnormal sounds [12].…”
Section: Introductionmentioning
confidence: 99%